Luminescent functionalized hydroxyapatite for bio-imaging - Leong, Sok Fong. (2010)
In this study, the synthesis of luminescent functionalized hydroxyapatite (HA) was investigated. Rare earth metal ions such as ytterbium (Yb3+) and erbium ions (Er3+) were doped into HA via the hydrothermal synthesis method. Fluoridated HA (FHA), achieved by exchanging hydroxyl ions in doped HA with fluoride ions via the pH-cycling method, was synthesized to investigate the luminescent property. The concentration of sodium fluoride (NaF), the medium for ion exchange, amount and ratio of Yb3+ and Er3+ were varied to study their effect on the luminescent intensity. The scanning electron microscopy (SEM) images and X-ray diffraction (XRD) patterns revealed that Yb-Er-HA has similar morphology and crystalline structure as pure HA. However the morphology and crystalline structure changes when F- ions were incorporated into the HA crystals. The FHA particles are no longer flower-shaped and it has a crystalline structure of that between fluorapatite (FA) and HA. Weak fluorescent signals in the infrared (IR)-to-visible light upconversion spectra were obtained from Yb-Er-FHA but not Yb-Er-HA. This shows that the incorporation of fluoride ions aided in the upconversion fluorescence of Yb-Er. However the upconversion spectra obtained from different synthesizing parameters revealed that there is no significant effect on the intensity of the peaks from the spectra. Although only weak fluorescent signals were obtained, this work provided a first demonstration that Yb-Er co doped FHA materials exhibit upconversion properties.